Hypselobarbus bicolor, a new species of large barb (Teleostei: Cyprinidae) from the Western Ghats of India - Knight, J. D. Marcus; Rai, Ashwin; D'souza, Ronald K.p.; Philip, Siby; Dahanukar, Neelesh (Zootaxa, 2016)
There has been much confusion around the identity of Hypselobarbus pulchellus, an endemic large barb of the Western Ghats. Recent works highlighted the fact that it is likely that two similar-looking species have been considered as H. pulchellus. A genetic analysis helps differentiate the two forms: viz., H. pulchellus and a new species, here described as H. bicolor sp. nov. Hypselobarbus bicolor can be distinguished from all other species of Hypselobarbus based on a combination of the following characters: two pairs of barbels, lateral line complete, with 34–36+1-2 pored scales, ½6/1/3½ scales in the transverse row; 11–12 predorsal scales; last simple dorsal ray weak, dorsal fin with 9½ branched rays, gill rakers short and simple, 4–6+11–12 on first gill arch; proximal end of fifth ceratobranchial slightly curved, with 5+3+2 teeth; overall coloration dark grey with an ill-defined silver- or bronze-coloured band running along length of body, two scales high, on lateral-line scale-row and row above it; fins devoid of any markings; and small, closely-placed tubercles restricted to the tip of the snout in large males.